THE ROLE OF THE PORTRAIT GENRE IN ART - Kenjayev Shavkat Qahramonovich; Amirqulov Ozod Erkin o'g'li (American Journals, 2023)
This article discusses the role of portrait genre in s antiques. Based on practical information, the author studied and analyzed specific aspects of the role of portrait genre in art based on existing scientific literature.
Keywords: Art, portrait, painting, sculpture, artist.